SIMULATION DESIGN OF HYBRID RENEWABLE ENERGY SYSTEMS AT THE COLLEGE OF SCIENCE IN THE UNIVERSITY OF ZAKHO, IRAQ - Yousif, Kamil M; Sadiq, Bilind S (Science Journal of University of Zakho, 2025)
Utilising renewable energy sources (RESs) instead of conventional power generation methods is crucial for mitigating climate change and global warming. As in other cities of the Kurdistan Region and Iraq, the national electricity outage crisis persists in Zakho, and power production via various sources remains necessary. In this study, the optimisation program ’Hybrid Optimisation Model for Electric Renewables’ HOMER Pro has been utilised to simulate two solar energy systems: grid-connected and off-grid. The systems are modelled for installation on the roof of the College of Science building at Zakho University, Iraq, which operates for 6 hours daily, from 9:00 a.m. to 3:00 p.m., Sunday to Thursday, while electricity consumption is extremely low during the summer weekends. Our findings confirm that the on-grid system is the more favourable option, with a cost of energy (COE) of 0.0194/kWh and a net present cost (NPC) of 295,544. On the other hand, the stand-alone design has a COE of 0.159/kWh and an NPC of 699,14. Moreover, the on-grid model derives 96% of its energy from renewable sources; whereas, the grid-independent design achieves 91.2%